2019
DOI: 10.3390/nu11102316
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Cancellous and Cortical Distal Femur by Fructose and Natural Mineral-Rich Water Consumption in Ovariectomized Female Sprague Dawley Rats

Abstract: Bone mineral density (BMD) and microstructure depend on estrogens and diet. We assessed the impact of natural mineral-rich water ingestion on distal femur of fructose-fed estrogen-deficient female Sprague Dawley rats. Ovariectomized rats drank tap or mineral-rich waters, with or without 10%-fructose, for 10 weeks. A sham-operated group drinking tap water was included (n = 6/group). Cancellous and cortical bone compartments were analyzed by microcomputed tomography. Circulating bone metabolism markers were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…suggested that for rats 10 weeks after ovariectomy, cancellous bone was damaged but not cortical bone in the distal femur [17]. It is possible that differences in the timing of intervention as well as species differences are responsible for the different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that for rats 10 weeks after ovariectomy, cancellous bone was damaged but not cortical bone in the distal femur [17]. It is possible that differences in the timing of intervention as well as species differences are responsible for the different results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is generally accepted that OVX results in cancellous bone loss. However, whether cortical bone loss or attenuated biomechanical properties occur in OVX mice is still controversial [1,3,17,[19][20][21]. Sharma et al suggested that increased vascular canal porosity in the cortical bone of OVX mice could be detected by high-resolution micro-CT [21].…”
Section: Introductionmentioning
confidence: 99%
“…are also required, as long as microbiological analyses to test the absence of parasites or pathogenic micro-organisms. If biological properties of NMSWs on different organ systems are established (e.g., urinary [53], digestive [54], respiratory [55], and gastrointestinal [56] tracts; bone [57]; and skin [58,59]), these must be confirmed by clinical and pharmacological analyses that state them as specific characteristics of each particular NMSW. Several of these parameters contribute to the classification of natural mineral waters: the 180 • C fixed residue, for example, defines the water mineral content (very low: <50 mg/L), low (<500 mg/L), medium (from 500 mg/L to 1500 mg/L) and high (>1500 mg/L).…”
Section: Natural Mineral Spring Waters (Nmsws) and Athletic Performancementioning
confidence: 99%
“…Our previous studies showed that drinking mineral-rich water could improve bone mechanical properties, bone mineral content, and bone development in rats ( 19 ). Several researchers found that the natural mineral water exerts more good effects on the trabecular number, bone surface density, and bone volumetric fraction in ovariectomized female Sprague Dawley rats ( 20 ). Furthermore, minerals in water are lower but can be more easily absorbed by the body due to its ionic species compared with mineral supplements which are used to treat serious acidosis in the clinic.…”
Section: Introductionmentioning
confidence: 99%